Irrigation in the age of agriculture 4.0: management, monitoring and precision - Silva, Alexsandro; Silva, Bruna; Souza, Claudinei; Azevedo, Benito; Bassoi, Luís; Vasconcelos, Denise; Bonfim, Guilherme; Juarez, Juan; dos Santos, Adão; Carneiro, Franciele (Revista Ciência Agronômica, 2021)
Technological evolution is essential to make irrigated agriculture more efficient in the use of water. Thus, this review article aims to contextualize irrigation in the age of agriculture 4.0 in order to address how these new technologies are impacting the rational use of water. With regard to the automation of irrigated systems, irrigation efficiency with moisture sensors, applications using smartphone, controllers and fertilizer injectors, as well as how their operation can promote irrigation, was addressed. Regarding irrigation management, the use of remote sensing as an option to determine crop evapotranspiration was contextualized, listing the types of spectral bands and sensors used to collect images (orbital, aerial and terrestrial), in the monitoring of crop water status. The importance of data collection in the delineations of management zones for precision irrigation and what possible advances can still be achieved with regard to obtaining and analyzing data were also discussed. Finally, it is concluded that, despite the high efficiency of automated irrigation systems, information of soil, climate and plant attributes obtained through the range of data provided by sensors will be responsible for mitigating the global impacts caused by irrigated agriculture in the near future, since this information can enhance irrigation, with maximum efficiency, thus reducing water consumption by agriculture.